Outcomes After Surgical Fixation of Posterior Sternoclavicular Physeal Fractures and Dislocations in Children. Issue 1 (January 2021) - Swarup, Ishaan; Cazzulino, Alejandro; Williams, Brendan A.; Defrancesco, Christopher; Spiegel, David; Shah, Apurva S.
Abstract : Background: Acute sternoclavicular fractures and dislocations (SCFDs) are a rare but important injury in pediatric patients. SCFDs are either true dislocations, or more commonly, physeal fractures in children. The reduction is advised given the proximity to surrounding vascular structures, and some authors advocate for routine fixation given rates of redisplacement after closed reduction. The purpose of the current study was to provide validated long-term functional outcome data following open reduction and surgical fixation of pediatric SCFDs, as well as provide injury and demographic information. Methods: This is a retrospective observational study with a subset of patients reporting functional outcomes. Patients under the age of 18 that had surgically managed acute posterior SCFD from 1990 to 2018 were included. A retrospective chart review was performed to obtain demographic, clinical, and surgical details. Patients with a minimum of 6-month follow-up were contacted to assess outcomes. Functional outcomes of interest included QuickDash, Visual Analog Scale pain rating, Single Assessment Numeric Evaluation of shoulder function, and PROMIS Upper Extremity questionnaire. Statistical analysis included descriptive statistics. Results: A total of 37 patients that sustained an acute posterior SCFD during the study period were included. The average age at the time of injury was 15.2±2.1 years and 89% were male. Patient-reported outcomes were obtained for 14 patients with a mean follow-up of 4.5 years. The mean QuickDash score was 5.1/100 with 0 being normal, and the mean Visual Analog Scale pain rating was 0.7/10. The mean Single Assessment Numeric Evaluation score was 96% with 100% being completely normal. The mean PROMIS score was 55 with 50 being the mean of the relevant reference population. Approximately 29% (4/14 patients) stated that their injury negatively affected their ability to participate in sports. Conclusions: There is a paucity of literature on functional outcomes after surgical management of pediatric acute posterior SCFD. Functional outcomes after surgery were satisfactory in this cohort with most patients being able to perform major activities of daily living. Additional future studies with larger cohorts and comparative groups are needed to better understand outcomes in this population. Level of Evidence: Level IV. Abstract : Supplemental Digital Content is available in the text.